(untitled) (Bangladesh Journal of Physics, 2022)
Microscopic description in the study of immiscibility and segregating properties of liquid metallic binary alloys has gained a renewed scientific and technological interests during the last eight years for the physicists, metallurgists and chemists. Especially, in understanding the basic mechanisms, from the point of interionic interaction, and how and why segregation in some metallic alloys takes place at and under certain thermodynamic state specified by temperature and pressure. An overview of the theoretical and experimental works done by different authors or groups in the area of segregation combining electronic theory of metals, statistical mechanics and the perturbative approach is presented in this review. Main attention in this review is focused on the static effects such as the effects of energy of mixing, enthalpy of mixing, entropy of mixing and understanding the critical behavior of segregation of alloys from the microscopic theoretical approach. Investigation of segregating properties from the dynamic effects such as from the effects of shear viscosity and diffusion coefficient is just becoming available. However, we have restricted this review only on static effects and their variation of impacts on different alloys. Bangladesh Journal of Physics, 27(2), 1-25, December 2020